Morphological and nutritional evaluation of ‘caraíba’ seedlings in different substrates using domestic sewage effluent for fertirrigation - de Brito, Raimundo Fernandes; Ferreira Neto, Miguel; da Silva Gomes, Jonath Werissimo [UNESP]; Lima Ferreira, Ana Luíza; da Silva Dias, Nildo; Barbosa de Lira, Raniere; Bezerra de Lima, Yuri; Nunes da Costa, João Paulo; Dos Santos Fernandes, Cleyton (Universidad Nacional de Colombia, 2020)
In this study, we evaluated the effects of fertigation with domestic sewage effluent and different substrates on the growth of Caraíba seedlings (Tabebuia aurea Benth). The experiment was accomplished in a greenhouse in Mossoró, RN. Five irrigation solutions (100% of water supply-WS, 100% of domestic sewage effluent – DS and dilutions of 75% DS + 25% WS, 50% DS + 50% WS e 25% DS + 75% WS) were tested and two substrates (75% soil + 25% bovine manure and 75% soil + 25% coconut fiber) using completely randomized design in subdivided plots with three replicates per treatment. Growth and development parameters were measured at 30, 60, 90, and 150 days after cultivation. The variables shoots height, collar diameter, height/diameter ratio, dry matter of root, shoots and total (root and shoots), shoots/root ratio, Dickson quality index, and nutritional evaluation of nitrogen, phosphorus, potassium and calcium were determinate. We verified that the use of domestic sewage increased growth and quality of caraíba seedlings, besides promoting nutrient accumulation in the plants grown in substrate of bovine manure plus soil with 100% application of domestic sewage in the fertigation.
Evaluación morfológica y nutricional de mudas de ‘caraíba’ fertirrigadas con efluente de alcantarillado doméstico con difentes sustratos
Keywords: Environmental sustainability; Forest species; Tabebuia aurea Benth; Water reuse